Original research Prevalence of use of advance directives, health care proxy, legal guardian, and living will in 512 patients hospitalized in a cardiac care unit/intensive care unit in 2 community hospitals - Kumar, Anil; Aronow, Wilbert; Alexa, Margelusa; Gothwal, Ritu; Jesmajian, Stephen; Bhushan, Bharat; Gaba, Praveen; Catevenis, James (Archives of Medical Science, 2010)
Introduction: The prevalence of use of any advance directives was 26% in 112 patients hospitalized in a cardiac care unit (CCU)/intensive care unit (ICU) in an academic medical center. Material and methods: We investigated in 2 community hospitals the prevalence of use of advance directives (AD), health care proxy (HCP), legal guardian (LG), and living will (LW) in 512 patients hospitalized in a CCU/ ICU approached for AD and HCP. Results: The use of AD was 22%, of HCP was 19%, of LG was 16%, and of LW was 5%. Conclusions: The use of AD was 22%, of HCP was 19%, of LG was 16%, and of LW was 5% in patients hospitalized in a CCU/ICU. Educational programs on use of AD and of HCP need to be part of cardiovascular training programs and of cardiovascular continuing medical education.